2022
DOI: 10.22376/ijpbs/lpr.2020.10.1.l51-59
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Screening and Identification of Cellulolytic Streptomyces corchorusii (Mn244066) From Soil Sample of Visakhapatnam

Abstract: Fifty one isolates of cellulolytic bacteria were isolated from cow dung and two soil samples were obtained from Kambalakonda Wildlife Sanctuary and RCD Biodiversity Park in Visakhapatnam, Andhra Pradesh by Enrichment method in basal salt medium with cellulose as substrate for degradation. The cellulolytic activity of the isolated bacteria was determined by the diameter of the zone of hydrolysis by Gram's iodine dye staining method. After primary screening, a total of fifty one isolates showed cellulolytic acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…STCH565-A has a high specific enzymatic activity when compared to another cellulolytic Streptomyces . For instance, a previous study reports 0.205 U/mg of cellulolytic activity ( Fatokun, Nwodo & Okoh, 2016 ) while another measurement eaches 4.38 U/mg ( Sujatha & Hemalatha, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…STCH565-A has a high specific enzymatic activity when compared to another cellulolytic Streptomyces . For instance, a previous study reports 0.205 U/mg of cellulolytic activity ( Fatokun, Nwodo & Okoh, 2016 ) while another measurement eaches 4.38 U/mg ( Sujatha & Hemalatha, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to temperature, earlier studies have also proved that pH near to neutral favour maximum production of enzyme through optimum growth of microorganisms. 19,21,26,37 In batch type culture, cellulase production reaches higher between 36 to 48 hrs of inoculation. 16, Predeep and Narasimha (2011) have used mutated fungi strain and found that production had started at maximum rate after 48 hrs and reached maximum at 7 days.…”
Section: Of Media Optimization and Environmental Conditionsmentioning
confidence: 99%
“…10,[12][13][14][15] For large scale production of this enzyme, cellulolytic microorganisms are preferred as they can be easily grown in larger quantity using various fermentation methods. [16][17][18]19 Optimization of environmental conditions enhances the production efficiency of microorganisms. 5,20,21 Majority of known microorganisms were isolated from common sources like garden soil and wood soil.…”
Section: Introductionmentioning
confidence: 99%